Friend or Foe: Lipid Droplets as Organelles for Protein and Lipid Storage in Cellular Stress Response, Aging and Disease - Florian Geltinger; Lukas Schartel; Markus Wiederstein; Julia Tevini; Elmar Aigner; Thomas K. Felder; Mark Rinnerthaler (Molecules, 2020)
Lipid droplets (LDs) were considered as a mere lipid storage organelle for a long time. Recent evidence suggests that LDs are in fact distinct and dynamic organelles with a specialized proteome and functions in many cellular roles. As such, LDs contribute to cellular signaling, protein and lipid homeostasis, metabolic diseases and inflammation. In line with the multitude of functions, LDs interact with many cellular organelles including mitochondria, peroxisomes, lysosomes, the endoplasmic reticulum and the nucleus. LDs are highly mobile and dynamic organelles and impaired motility disrupts the interaction with other organelles. The reduction of interorganelle contacts results in a multitude of pathophysiologies and frequently in neurodegenerative diseases. Contacts not only supply lipids for β-oxidation in mitochondria and peroxisomes, but also may include the transfer of toxic lipids as well as misfolded and harmful proteins to LDs. Furthermore, LDs assist in the removal of protein aggregates when severe proteotoxic stress overwhelms the proteasomal system. During imbalance of cellular lipid homeostasis, LDs also support cellular detoxification. Fine-tuning of LD function is of crucial importance and many diseases are associated with dysfunctional LDs. We summarize the current understanding of LDs and their interactions with organelles, providing a storage site for harmful proteins and lipids during cellular stress, aging inflammation and various disease states.